Dickinsonia: mobile and adhered. (12th July 2022) - Ivantsov, Andrey; Zakrevskaya, Maria
Abstract: The classical genus of Ediacaran macroorganisms, Dickinsonia, was part of an extensive benthic marine community inhabiting the fields of microbial mats. The remains of Dickinsonia are commonly preserved in the position of adhesion to the habitat substrate. However, these were mobile organisms. In addition to the already known feeding traces of Dickinsonia, structures described as traces of motor activity are reported. Long parallel furrows, extending from the posterior end of the body imprint, are interpreted as imprints of ridges left by an organism moving along the surface of the substrate. Groups of differently shaped grooves laying in the depression that enhalo the Dickinsonia body imprints or accompany their individual areas are interpreted as imprints of ridges and cords of mucous material. They are considered to represent structures of self-determined stretching and lift-off of the body margins from the substrate. The rings and arcs of silt- and sand-sized mineral particles bordering the body imprints are composed of material that was supposedly brushed off from the surface of the microbial mat by Dickinsonia . They are considered traces of the adhesion of these organisms to the substrate. Accumulations of multidirectional pulling and tear-off structures, lacking the body imprint but accompanied by the joint plane passing into the overlying sediment and cutting through the bedding, are interpreted as escape traces. The dual modality of the behaviour (attachment and mobility) could indicate the adaptability of Dickinsonia to life in extremely shallow-water environments.